1996
DOI: 10.4319/lo.1996.41.3.0540
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide formation: The interaction of ultraviolet radiation and dissolved organic carbon in lake waters along a 43–75°N gradient

Abstract: Abstract-Hydrogen peroxide (H,O,) formation rates (nM h-l), photoproductive capacity (nM W-l h-l m-*), and H202 formation efficiency (bH202) were measured on water samples exposed to a standard light source with a spectral composition similar to natural sunlight. Samples were from lakes and wetlands with varying levels of dissolved organic C (DOC), P, Fe, Ca, and pH. The relationship between H,O, formation rates and DOC was a power function @ItO = 49.65 DOC1-71; r* = 0.94), whereas the relationships between fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
147
7

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(160 citation statements)
references
References 16 publications
6
147
7
Order By: Relevance
“…For samples other than the Elizabeth River, there is no statistically significant relationship between peroxide production and [DOC]. Scully et al (1996) observed a power relationship between H 2 O 2 production and DOC content in freshwaters, similar to that observed for the Elizabeth River sample. Whether relationships of this type should be extended to seawater systems is still unclear.…”
Section: Peroxide Productionsupporting
confidence: 65%
See 3 more Smart Citations
“…For samples other than the Elizabeth River, there is no statistically significant relationship between peroxide production and [DOC]. Scully et al (1996) observed a power relationship between H 2 O 2 production and DOC content in freshwaters, similar to that observed for the Elizabeth River sample. Whether relationships of this type should be extended to seawater systems is still unclear.…”
Section: Peroxide Productionsupporting
confidence: 65%
“…H 2 O 2 production in Elizabeth River water was similar to that of freshwater systems, such as Lake Ontario (160-1473 nM h À 1 ) and other temperate lakes (695-2120 nM h À 1 ) (Scully et al, 1996). Surface waters with substantial terrigenous run-off influence exhibited the greatest production of both H 2 O 2 and MHP, with the majority of production occurring at wavelengths less than 320 nm.…”
Section: Peroxide Productionmentioning
confidence: 69%
See 2 more Smart Citations
“…Because DOM is an important component of carbon budgets in aquatic ecosystems, an understanding of how photodegradation alters DOM bioavailability is critical to understand carbon fluxes through the landscape. In contrast to the positive effects of increased substrate availability on bacterial metabolism, photodegradation also exerts indirect negative effects on aquatic bacteria through the production of free radicals and reactive oxygen species (ROS) (e.g., singlet oxygen, peroxides, and superoxides) (Scully et al 1996). These by-products of the photodegradation process are short-lived, but nevertheless inhibit bacterial growth and production (Lund and Hongve 1994;Henle and Linn 1997;Anesio et al 2005).…”
Section: Introductionmentioning
confidence: 99%